ANALISIS PERHITUNGAN PAJAK PENGHASILAN PASAL 25 WAJIB PAJAK - Inaya Zahra; Widya Fadla Wibowo; Ginda Fuad Badilah; Dini Vientiany (INTERNATIONAL, Journal of Sharia Business Management, 2026)
This study aims to analyze the calculation of Article 25 Income Tax for taxpayers and identify the factors influencing the implementation of tax obligations in accordance with tax regulations in Indonesia. The research method used is a qualitative approach with a descriptive research type. Research data were obtained through literature studies, documentation, and various scientific references related to taxation, especially Article 25 Income Tax. The results of the study indicate that the calculation of Article 25 Income Tax is carried out based on the previous year’s payable income tax by considering taxable income, fiscal corrections, and applicable tax administration procedures. In addition, the level of tax understanding, taxpayer compliance, implementation of digital-based administrative systems, and supervision by tax authorities are important factors affecting the accuracy of tax calculations. The implementation of Article 25 Income Tax also has a positive impact on the stability of tax payments, increasing taxpayer compliance, and optimizing state revenue. Therefore, improving tax education and strengthening the tax administration system are necessary so that the implementation of tax obligations can run more effectively, transparently, and in accordance with applicable tax regulations.